Images mobiles et cadre rituel dans le Bwiti Disumba de la Nyanga (Gabon). - Maxime de Formanoir (Images Re-Vues)
Contrary to what has long been reported about figure sculptures from other parts of Western Equatorial Africa, effigies from southwestern Gabon interpreted as « ancestor figures » have been described up to now as « immutable and immobile in their role as guardians of the relics » (Louis Perrois and Charlotte Grand-Dufay, Punu, trad. Isabel Ollivier, Milan, 5 Continents Editions, 2008, p. 36). Recent field surveys and interviews in Nyanga Province and inhabitants of Estuary Province, however, attest to the mobility of the statuary still used within certain initiation societies, such as the sculptures that top « reliquary bundles » kept by adepts of Bwiti Disumba. This paper examines these devices. Sometimes carried over long distances, they periodically go to « the bush ». Dealing with the « animation » of statuary in such contexts, this study also aims to shed light on what is at stake, in this matter, outside the framework of ceremonies.